Manajemen Strategi Keamanan di Pulau Bali - Reinhard Habonaran Nainggolan; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe research undertaken at the Special Crime Investigation Directorate of Bali Regional Police aims to analyze the appropriate strategic management applied in the Special Crime Investigation Directorate in order to realize the security of the country. This research uses descriptive qualitative research method with data collection technique that is observation, interview and document study. Technique of examination and testing of data validity using triangulation of source and triangulation technique. Data analysis is done by data reduction, data presentation and withdrawal of conclusion and verification. Based on the result of the research, it can be concluded that the appropriate strategic management applied in the Special Crime Investigation Directorate is the improvement of professional, proportional and accountable police human resources in conducting special investigation and investigation of crime, supported by knowledge about law and legislation as well as information technology based capability and skill. The development of INP's human resources must be transparent and accountable with clear reward and punishment mechanisms, so that INP personnel can be realized that is professional, independent and reliable. Operational improvement, supported by a dynamic budgeting system following the development of security and public order is performance-based budgeting and supporting infrastructure, with information technology-based, to achieve maximum results to achieve strive for excellence to the community in order to realize national security.